2007
DOI: 10.1037/0033-3204.44.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of early memories as a predictor of early therapeutic alliance.

Abstract: The present study aims to empirically explore the relationship between clinician-rated early memories (EMs) and patient ratings of alliance that were obtained after a therapeutic model of assessment (TMA; Finn & Tonsager, 1997; Fischer, 1994). This study utilizes the Social Cognition and Object Relations Scale (SCORS; Westen, 1995) to obtain information from early memory narratives about an individual's level of object representations. With data gathered from 57 participants, the authors examined whether an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…The finding that patients' greater alienation and insecure attachment were associated to worse patient alliance perception supports previous findings of a significant relation between patient object relations and patients' alliance perception (Pinsker‐Aspen et al ., ; Piper et al ., ), and are inconsistent with studies that failed to find a significant link (Goldman & Anderson, ; Mallinckrodt et al ., ). In the case of Goldman and Anderson's study, most of their effects, although not statistically significant, were in the same direction as our study.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that patients' greater alienation and insecure attachment were associated to worse patient alliance perception supports previous findings of a significant relation between patient object relations and patients' alliance perception (Pinsker‐Aspen et al ., ; Piper et al ., ), and are inconsistent with studies that failed to find a significant link (Goldman & Anderson, ; Mallinckrodt et al ., ). In the case of Goldman and Anderson's study, most of their effects, although not statistically significant, were in the same direction as our study.…”
Section: Discussionmentioning
confidence: 99%
“…OR refers to how persons view themselves and how they come to interact or relate to others. Typically, this involves prototypes of ‘objects’, which are borne from interactions with primary caregivers in childhood (Pinsker‐Aspen, Stein, & Hilsenroth, ; Westen, ). Conceptually, patient OR functioning has logical parallels to the therapeutic relationship.…”
mentioning
confidence: 99%
“…For example, patients who are overly detached, cold/distant and experienced low self‐esteem have reported vis‐à‐vis poorer quality working alliances/therapeutic bonds (e.g., Beretta et al, ; Hersoug, Monsen, Havik, & Hoglend, ; Saunders, ). Similarly, Pinsker‐Aspen et al () summarized prior work noting patient OR and attachment style as a significant determinant of how an individual may enter into a therapeutic relationship, how the relationship might develop and how psychotherapeutic process could unfold.…”
mentioning
confidence: 99%
“…This finding is consistent with previous attachment research, which indicates that representations of others are related to the capacity to establish trust and closeness (Bowlby, 1988;Diener & Monroe, 2011;Mallinckrodt et al, 2009;Mikulincer & Shaver, 2007). In addition, Pinsker et al (2007), and Ryan and Cicchetti (1985) assessed object relations as they appear in an early memories task, while we assessed them as they appear in Rorschach responses. One can argue that early memories represent material that is more accessible to patients; however, Rorschach responses represent material that is less close to the surface of consciousness and as such might represent a different quality of object representations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, attachment style and object relations have been found to be predictors of alliance quality (Eames & Roth, 2000;Hilliard, Henry, & Strupp, 2000;Joyce & Piper, 1998;. For example, Pinsker-Aspen et al (2007) found that patients with less complexity, differentiation, and integration in representations of self and others as captured by their early memories reported a weaker alliance with their therapists compared with patients who had more complexity and integration in their representations. This finding appears to be consistent with findings in an earlier study in which object relations as captured by early memories accounted for 30% of the variance in alliance scores (Ryan & Cicchetti, 1985).…”
Section: Object Relations and The Therapeutic Alliancementioning
confidence: 92%